2005
DOI: 10.4103/0971-9261.16469
|View full text |Cite
|
Sign up to set email alerts
|

Role of laparoscopic cholecystectomy in children

Abstract: ABSTRACT ABSTRACT ABSTRACTThe present study is undertaken to establish the usefulness of laparoscopic cholecystectomy and to know its merits and demerits as compared to open cholecystectomy in children. In all, 28 patients who underwent cholecystectomy (8 open and 20 laparoscopic cholecystectomy) in B.Y.L. Nair hospital between July 1999 and March 2004 were analyzed. Calculous cholecystitis was found to be the most common indication for surgery. Operative time for laparoscopic cholecystectomy was more than tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 6 publications
1
7
3
Order By: Relevance
“…Maximum numbers of children were between 11 and 16 years of age (69.6%) in our study. This is in variance with some studies which have reported it to be more common between 5 and 10 years of age (13,14). In a study of 128 patients undergoing paediatric cholecystectomy, mean age was found to be 10 years (15).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Maximum numbers of children were between 11 and 16 years of age (69.6%) in our study. This is in variance with some studies which have reported it to be more common between 5 and 10 years of age (13,14). In a study of 128 patients undergoing paediatric cholecystectomy, mean age was found to be 10 years (15).…”
Section: Discussioncontrasting
confidence: 99%
“…The frequency of acalculus cholecystitis in children has been reported as 30–50% of cholecystitis when compared to 2–17% of cases in adults (17). In our study, acalculus cholecystitis was seen in 21.4% children of cholecystitis which is in contrast to another study from India with frequency of 9% (13).…”
Section: Discussioncontrasting
confidence: 98%
“…The incidence of gallstones among boys and girls is almost equal, with a slightly high incidence among boys. [51011] The sex ratio in our study was slightly in favour of females. LC in children differs from that in adults in various aspects.…”
Section: Discussioncontrasting
confidence: 48%
“…The benefi ts of laparoscopic cholecystectomy include decreased pain and ileus after surgery, shortened hospitalization, and improved cosmetic (1). Oak et al (2) arrived to the same conclusion when comparing traditional cholecystestomy with laparoscopic cholecystectomy.…”
mentioning
confidence: 74%